THE EFFECT OF WORKING CAPITAL ACTIVITIES ON COMPANY PROFITABILITY (At PT. Telekomunikasi Indonesia, Tbk) - Syafariah, Anita (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
PT. Telekomunikasi Indonesia, Tbk is an information and communication company as well as a service provider and operator of a complete telecommunications network in Indonesia. TELKOM claims to be the largest telecommunications company in Indonesia, with 12.4 million fixed telephone subscribers and 23.5 million cellular subscribers. The company was founded in 1884 and is headquartered in Bandung, Indonesia. With adequate working capital and good sources and use of working capital, it is very possible for the company to operate optimally with efficient use of working capital. Based on the results of this study, it is known that the calculation results for a period of five periods are known that the working capital turnover is in a minus condition every year and the company's profitability has decreased every year, namely for working capital turnover in 2007 which was -2.273, in 2008 it was -1.244, in 2007 2009 is -0.990, 2010 is -1.879, and 2011 is -8.203. For the level of profitability achieved by PT. Telekomunikasi Indonesia, Tbk during the period 2007-2011 has decreased every year. The highest condition was achieved in 2007 at 15.67% and the lowest condition occurred in 2011 at 10.64%. In testing the hypothesis that working capital has no significant effect on the profitability of own capital.